PENGARUH PEMBERIAN ABU VULKAN MERAPI DAN FREKUENSI PENYIRAMAN TERHADAP PERTUMBUHAN TANAMAN BUAH NAGA (Hylocereus undatus (Haworth) Britton & Rose) SETELAH PANGKAS BENTUK - , DIYAR OKTA PRATAMA; , Prof. Dr. I r. Prapto Yudono, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aimed to measure the effect of volcanic ash of Mount Merapi in retaining water loss from the rooting medium and determine the effect of frequency of water on the growth of dragon fruit (Hylocereus undatus (Hawort ) Britton & Rose) after trim form. The experiment was conducted Keburuhan sand land held in the Faculty of Agriculture , Gadjah Mada University , located in Purworedjo , in June 2012 to Oktober2012 . The design used was a 3 x 3 factorial arranged in a randomized complete ( RAKL ) with 3 blocks as replicates. The first factor is the Mount Merapi volcanic ash given 1 kg / pot , 2 kg / pot , and 3 kg / pot . The second factor is the frequency of watering with a time of 3 days , 6 days , and 9 hari.Penanaman this plant has been carried out in October 2011, so this time the plant has from 8 to 9 month. Planted in 80 cm diameter concrete bus and fertilizer cage as much as 20 kg / pot and each pot contains 3 seeds . Mount Merapi volcanic ash granting dose of 3 Kg able to withstand water loss from the media perakaran.Frekuensi 9 days watering can provide optimal growth taaman dragon fruit (Hylocereus undatus (Hawort ) Britton & Rose) . Treatment ash volcanic Mount Merapi and the frequency of watering at the age of 7 interacting week to variable diameter shoots ash volcanic 2 kg with the frequency of watering 3 days and 3 kg of volcanic ash with the frequency of watering 9 days .